Combined Action of Piperitenone Epoxide and Antibiotics Against Clinical Isolates of Staphylococcus aureus and Escherichia coli - Alexopoulos, Athanasios; Kimbaris, Athanasios C.; Plessas, Stavros; Mantzourani, Ioanna; Voidarou, Chrysa; Pagonopoulou, Olga; Tsigalou, Christina; Fournomiti, Maria; Bontsidis, Christos; Stavropoulou, Elisavet; Papaemmanouil, Virginia; Bezirtzoglou, Eugenia (Frontiers in Microbiology, 2019)
The aim of this study was to determine the antimicrobial efficiency of piperitenone epoxide (PEO) - a principal component of various aromatic plants' essential oil - in combination with various antibiotics against twenty eight strains of Staphylococcus aureus and ten strains of Escherichia coli isolated from clinical samples. Mentha spicata’s essential oil, initially collected by hydrodistillation, was then subjected to flush column chromatography affording PEO of high purity. Minimum Inhibitory Concentrations (MIC) of PEO alone and in combination with various concentrations of synthesized antibiotics was assessed by using the micro dilution method. The combined action was estimated calculating the Fractional Inhibitory Concentration Index (FICI) from checkerboard assays. Our results showed that the average MIC (mg/L) of PEO alone against E. coli was 512 ± 364.7 μg/mL which was significantly higher than 172.8 ± 180.7 μg/mL observed for S. aureus. From checkerboard assays, FIC values below the 0.5 index, indicating synergy, were observed for 59% of the synthesized drugs tested. Twelve percent of FIC index values were between 0.5 and 1 indicating additive effects, while 21% were indifferent. According to our results, PEO could be a promising antimicrobial compound when combined with specific antibiotics and deserves further study.